EDUKASI PENGENALAN DAMPAK NEGATIF ZAT PEWARNA BERBAHAYA PADA MAKANAN JAJANAN TERHADAP KESEHATAN DI SMA NEGERI 14 MAKASSAR - Rahmawati Rahmawati; Anita Anita; Tuty Widyanti (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2022)
Snack food in schools is very at risk of getting biological or chemical contamination that interferes with health. One of the food additives that is added for the purpose of giving color to food or drinks to have an attractive appearance is synthetic dyes. Synthetic dyes that are widely used in the community are rhodamine B and methanyl yellow. The impacts that can be caused, especially synthetic textile dyes, are skin rashes, runny nose, asthma, bruising and shock. To increase knowledge and change behavior, educational interventions are needed. Therefore, it is necessary to introduce additives and their kinds, as well as those which are harmful to health. The PkM implementation team from the Muhammadiyah Makassar Health Polytechnic participated in organizing educational activities at SMAN 14 Makassar to provide information in the form of counseling to students (i) and teachers about the introduction of harmful dyes and the negative impact of consuming street food in schools that contain dyes. Thus, it can be concluded that in general the activity went well and smoothly as evidenced by the presentation of students who could answer the post test correctly by 85.11%.